ANALYSIS OF DETERMINANTS OF AVERAGE COMMUNITY CONSUMPTION IN BALI PROVINCE - Sherina Eknanda Juliantika; Made Dwi Setyadhi Mustika (INTERNATIONAL JOURNAL OF ECONOMIC LITERATURE, 2025)
The level of consumption is one of the indicators for determining the economic performance of a country. Measuring the level of consumption is important to gauge welfare and understand the conditions and quality of the population in economic development. This study aims to analyze the simultaneous and partial effects of the number of micro, small, and medium enterprises (MSMEs), the labor force participation rate (LFPR), and economic growth on the average per capita consumption in Bali Province. The data used is panel data from the years 2015 - 2023 from the regencies/cities in Bali Province, obtained from the Department of Cooperatives and MSMEs and the Central Statistics Agency. The analytical techniques used are descriptive analysis and multiple linear regression. The results show that simultaneously, the number of MSMEs, LFPR, and economic growth significantly affect the average per capita consumption in Bali Province. Partially, the number of MSMEs has a positive and significant effect on the average per capita consumption, while the LFPR has a negative and significant effect on the average per capita consumption. Economic growth, when considered partially, does not significantly affect the average per capita consumption.